The Judicial implementation of the right to education in Brazil: analysis from the STF's perspective (Revista do Tribunal Regional Federal da 3ª Região, 2014)
The article will present, from the perspective of two STF jurisprudential precedents, how the issue of implementing the right to education through the judicial system has been resolved, distinguishing one hypothesis in which it was characterized as a subjective public right from another in which the Constitutional Court limited itself.
Keywords: education; social right; judicial implementation; subjective right; immediate justiciability; childcare; illiteracy